2016
DOI: 10.1097/md.0000000000005261
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric visceral leishmaniasis in northwest of Iran

Abstract: Leishmaniasis is one of the major health problems in Iran. Although the incidence of visceral leishmaniasis (VL) is reported almost everywhere, the northwestern Iran is one of the major endemic regions.To do this study, clinical, laboratory as well as disease characteristics of children admitted to Children Cure and Health Hospital, Tabriz University of Medical Sciences, were examined as the reference hospital for the treatment of VL in northwestern Iran.In this study, 156 children hospitalized in a pediatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 24 publications
3
20
3
Order By: Relevance
“…Despite the visceral leishmaniasis infection age distribution throughout Iran in previous studies (12), our findings showed that most of the studied dogs were less than five-years-old, but the highest number of infections was in the age group of 5 -10 years, which probably indicates that this age group is more sensitive to visceral leishmaniasis in this region. Although the bone marrow and lymph nodes have many parasites, according to studies, conjunctiva, oral mucosa or snout and blood are both reliable and suitable for molecular studies because the sample source in dogs is important for accurately determining the contamination.…”
Section: Discussioncontrasting
confidence: 83%
“…Despite the visceral leishmaniasis infection age distribution throughout Iran in previous studies (12), our findings showed that most of the studied dogs were less than five-years-old, but the highest number of infections was in the age group of 5 -10 years, which probably indicates that this age group is more sensitive to visceral leishmaniasis in this region. Although the bone marrow and lymph nodes have many parasites, according to studies, conjunctiva, oral mucosa or snout and blood are both reliable and suitable for molecular studies because the sample source in dogs is important for accurately determining the contamination.…”
Section: Discussioncontrasting
confidence: 83%
“…Anemia, slight-to-moderate liver enzyme elevation, and increased ESR and CRP were present in all (100%) of our patients at presentation, which conforms to the majority of previous studies (1,5,13). However, in a study by Abdinia et al (6), aspartate aminotransferase (AST) and alanine aminotransferase (ALT) elevation were reported in only 25% and 11% of patients, respectively. This can be seen as a major difference, especially considering that the study in question was performed in a region that neighbors the south-eastern region of Turkey (Northwest of Iran).…”
Section: Physical Examination and Laboratory Findingssupporting
confidence: 91%
“…Lymphadenopathy was the third most common finding in our study group with a frequency of 50%, however, Miao et al (10) reported that it was present in only 33% of their patients. In the current study, bleeding manifestations were observed in the form of petechiae in 2 (11.1%) patients, Krepis et al (11) reported bleeding manifestations in 7% of their patients (12), while Abdinia et al (6) reported petechiae and purpura in 11.5% of their study group. The classic triad of VL is comprised of fever, splenomegaly and pallor (13,14).…”
Section: Physical Examination and Laboratory Findingssupporting
confidence: 40%
See 1 more Smart Citation
“…Poor treatment outcome related to the delay in diagnosis was reported in other similar studies [25, 31]. The implication of this finding is the importance of early diagnosis, as the disease is completely curable with timely treatment [32]. Furthermore, transmission can be reduced through early case detection followed by complete treatment [10].…”
Section: Discussionmentioning
confidence: 87%